Bonjour,
Il suffit de remplacer [tex]x[/tex] par 5 dans les égalités.
4[tex]x[/tex] + 1 = 4 × 5 + 1 = 20 + 1 = 21
5[tex]x[/tex] - 4 = 5 × 5 - 4 = 25 - 4 = 21
Pour [tex]x[/tex] = 5, on a donc :
4[tex]x[/tex] + 1 = 5[tex]x[/tex] - 4
Cette égalité est vraie pour [tex]x[/tex] = 5
[tex]x[/tex] - 6 = 5 - 6 = -1
2[tex]x[/tex] - 11 = 2 × 5 - 11 = 10 - 11 = -1
Pour [tex]x[/tex] = 5, on a donc :
[tex]x[/tex] - 6 = 2[tex]x[/tex] - 11
Cette égalité est vraie pour [tex]x[/tex] = 5
En espérant t'avoir aidé :)